ANALISIS MODEL POLITICAL MARKETING SEBAGAI STRATEGI MENINGKATKAN PARTISIPASI POLITIK PEREMPUAN MINANGKABAU DI PARLEMEN - Yesi Elsandra; Tiara Turay; Nadia Insani (MANAJEMEN, 2025)
This study aims to analyze the low participation of female Minangkabau legislative members in West Sumatra. Women in Minangkabau culture and customs have a strong influence in customs. But this privilege has not been accompanied by equality in political participation. Minangkabau women can use political marketing strategies to compete with other candidates so that the mandate of the law of 30% female representation in parliament can be realized. The method used in this study is quantitative descriptive. The results of the study indicate that the marketing approach can be used in political activities called political marketing. Political marketing activities in the form of push marketing, pull marketing and pass marketing have a significant influence on constituents' decisions to elect legislative member